On-line Competency Based Learning in World Language Classes - Perdomo, Aida Cristina (2021)
Twenty First century educators must be courageous and take risks in redirecting education systems towards sustainable development and inclusive education, all with an emphasis on the formation of adaptable and transferable skills. In addition, these professionals must navigate between ICT and the need to focus the teaching-learning process on the student. After Covid-19,  teachers know that uncertainty is the only thing that is certain and that their safest tools are their own instincts to find the direction for their students. This investigative article is based on a documentary review of  skills-based education through competencies, on line learning, and world language instruction based on UNESCO's 2030 vision. It was concluded that on line learning came to educationto stay and it is important to recognize the needs of an ICT-personalization balance skills-based learning as we are educating individuals who need strong and healthy human connections.